2012
DOI: 10.1016/j.neulet.2012.03.070
|View full text |Cite
|
Sign up to set email alerts
|

Dipyrone attenuates acute sickness response to lipopolysaccharide in mice

Abstract: Sickness behavior appears to be the expression of a central motivational state that reorganizes the organism's priorities to cope with infectious pathogens. To evaluate the effect of dipyrone in lipopolysaccharide (LPS)-induced sickness behavior, mice were subjected to the forced swim test (FST), tail suspension test (TST), dark-light box test, open field test, sucrose preference intake test and food intake test. LPS administration increased the immobility time in the TST, increased the time spent floating in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…This long-lasting effect may have influenced the performance of the animals in the light-dark and forced swim tests, two behavioral assessments with a considerable locomotor component. Usually, studies refer this effect as “depressed locomotor activity” [45, 46]. Thus, it is difficult to dissociate sickness behavior from depressive-like behavior in the present study.…”
Section: Discussionmentioning
confidence: 92%
“…This long-lasting effect may have influenced the performance of the animals in the light-dark and forced swim tests, two behavioral assessments with a considerable locomotor component. Usually, studies refer this effect as “depressed locomotor activity” [45, 46]. Thus, it is difficult to dissociate sickness behavior from depressive-like behavior in the present study.…”
Section: Discussionmentioning
confidence: 92%
“…Here, LPS administration depressed locomotor activity in the OFT, and pifithrin-μ treatment reversed this effect. The lightdark box test is a characteristic tool used in the assessment of behaviors associated with anxiety [17,18] . Our data showed that LPS elicited an anxiogenic-like response in the light-dark box test, exemplified by a significant increase in the latency to first transition and a significant decrease in the total number of transitions.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, a recent study demonstrated that acute oral administration of high doses of the analgesic agent dipyrone displayed antidepressant-like effects in the mouse model of acute inflammation elicited by LPS [32]. Additionally, a recent publication showed a clear relationship between chronic pain and depression, in a rat model of inflammatory arthritis elicited by the intra-articular injection of CFA, via mechanisms involving the upregulation of IDO [17].…”
Section: Discussionmentioning
confidence: 99%
“…Independent groups were used to analyse the effects of anti-inflammatory or antidepressant drugs on paw edema or depression-like behavior. The schedules of treatment were determined on the basis of previous literature or on pilot experiments [15,31,32,33,34]. …”
Section: Methodsmentioning
confidence: 99%